Abnormalities associated with progressive aortic vascular dysfunction in chronic kidney disease - Ameer, Omar Z.; Boyd, Rochelle; Butlin, Mark; Avolio, Alberto P.; Phillips, Jacqueline K. (Frontiers in Physiology, 2015)
Increased stiffness of large arteries in chronic kidney disease (CKD) has significant clinical implications. This study investigates the temporal development of thoracic aortic dysfunction in a rodent model of CKD, the Lewis polycystic kidney (LPK) rat. Animals aged 12 and 18 weeks were studied alongside age-matched Lewis controls (total n=94). LPK rodents had elevated systolic blood pressure, left ventricular hypertrophy and progressively higher plasma creatinine and urea. Relative to Lewis controls, LPK exhibited reduced maximum aortic vasoconstriction (Rmax) to noradrenaline at 12 and 18 weeks, and to K+ (12 weeks). Sensitivity to noradrenaline was greater in 18-week-old LPK versus age matched Lewis (effective concentration 50%: 24×10-9 ± 78×10-10 vs. 19×10-8 ± 49×10-9, P<0.05). Endothelium-dependent (acetylcholine) and -independent (sodium nitroprusside) relaxation was diminished in LPK, declining with age (12 vs. 18 weeks Rmax: 80 ± 8% vs. 57 ± 9% and 92 ± 6% vs. 70 ± 9%, P<0.05, respectively) in parallel with the decline in renal function. L-Arginine restored endothelial function in LPK, and L-NAME blunted acetylcholine relaxation in all groups. Impaired nitric oxide synthase (NOS) activity was recovered with L-Arginine plus L-NAME in 12, but not 18-week-old LPK. Aortic calcification was increased in LPK rats, as was collagen I/III, fibronectin and NADPH-oxidase subunit p47 (phox) mRNAs. Overall, our observations indicate that the vascular abnormalities associated with CKD are progressive in nature, being characterised by impaired vascular contraction and relaxation responses, concurrent with the development of endothelial dysfunction, which is likely driven by evolving deficits in NO signalling.